2015
DOI: 10.22610/imbr.v7i4.1163
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Celebrity Credibility on Consumer’s Purchase Intention toward the Footwear Industry in Malaysia: The Mediating Effect of Attitude toward Advertisement

Abstract: Practices of using celebrities as spokespeople for commercialized products are continuously favoured toward the effort of marketing and positioning. The popularity of celebrity advertising is founded upon advertiser’s belief on message credibility by well-known personalities to achieve greater attention, recall and behavioural intention among consumers. The present study assesses the impact of celebrity credibility on the underlying purchase intention of Malaysian consumers toward the footwear industry, by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…However, most studies have used source attractiveness and source credibility models to explain the efficacy of celebrity endorsement as the source models factor in the effect of celebrity characteristics on the endorsed product as perceived by the consumers (Chin, Isa, & Alodin, 2019;Ong & Ong, 2015;Trivedi, 2018a).…”
Section: Celebrity-owned Restaurants (Celebrity Endorsement)mentioning
confidence: 99%
“…However, most studies have used source attractiveness and source credibility models to explain the efficacy of celebrity endorsement as the source models factor in the effect of celebrity characteristics on the endorsed product as perceived by the consumers (Chin, Isa, & Alodin, 2019;Ong & Ong, 2015;Trivedi, 2018a).…”
Section: Celebrity-owned Restaurants (Celebrity Endorsement)mentioning
confidence: 99%
“…Attitude is defined as an individual's personal evaluation, emotional feelings, and actions tendency towards affairs, objects, ideas, and behaviours [19]. It acts as a basis to individual's willingness in behaving under a specific manner [65,66]. The concept of attitude has been vastly applied in the marketing context since the 1960s [66].…”
Section: Attitude Towards Celebrity Endorsement and Purchase Intentionmentioning
confidence: 99%
“…It acts as a basis to individual's willingness in behaving under a specific manner [65,66]. The concept of attitude has been vastly applied in the marketing context since the 1960s [66]. Gresham and Shrimp [67] firstly proposed the impact of attitude on behaviour in marketing.…”
Section: Attitude Towards Celebrity Endorsement and Purchase Intentionmentioning
confidence: 99%
“…Purchase intention is another measure of advertising effectiveness and is often used by studies conducting empirical investigations of consumer behaviour after being exposed to advertising stimuli (Vanwesenbeeck, Walrave & Ponnet, 2017). Recent studies found positive relationship between endorser credibility and purchase intention (Gupta, Nawal & Verma, 2015;Ong & Ong, 2015). Sallam and AbdulWahid (2012) found endorser credibility effect on Yemeni male consumers' attitude towards advertising and purchase intention.…”
Section: Endorser Credibility Attitude Toward Advertising and Purchamentioning
confidence: 99%